A comparative study of the E. faecalis antibiofilm efficacy of photoactivated curcumin, chlorophyll and riboflavin - Riski Setyo Avianti; Sri Kunarti; Ari Subiyanto (Dental Journal (Majalah Kedokteran Gigi), 2020)
Background: Photosensitisers play a vital role for reactive oxygen species (ROS) production in diode laser 405 nm therapy. Curcumin, chlorophyll and riboflavin have been used and viewed in several studies as effective photosensitisers for the elimination of Enterococcus faecalis (E. faecalis), a persistent microorganism that may cause endodontic failure. While each has given valuable and promising results as an alternative endodontic irrigant, no study has compared the efficacy of these three natural dyes. Purpose: To prove that the photosensitiser curcumin in diode laser 405 nm therapy is more effective for E. faecalis biofilm degradation than chlorophyll and riboflavin, and that a duration of irradiation of 90 seconds is more effective than 60 seconds. Methods: The biofilm monospecies E. faecalis was divided into two microplates with 96-well according to the irradiation periods: 60 seconds (Group 1) and 90 seconds (Group 2). Each group contained one control (without a photosensitiser) and three treatments were carried out by adding the photosensitisers curcumin, chlorophyll and riboflavin, where each treatment contained eleven samples. After irradiation for 60 seconds and 90 seconds, a crystal violet assay was carried out for each group. Results: The one-way ANOVA test showed a significant difference between groups based on the irradiation period. Tukey’s test showed each treatment in each group also showed a significant difference (p<0.05) with curcumin as the best substance to cause biofilm degradation in both groups. The duration of the irradiation showed that the longer the biofilm was illuminated, the lower the absorbance value or optical density (OD). Conclusion: Curcumin irradiated for 90 seconds gives better biofilm degradation on E. faecalis due to its natural properties and molecular structure, highlighting its efficacy in photodynamic therapy